Centralized vs. decentralized wage formation: The role of firms' production technology - Boris Hirsch; Christian Merkl; Steffen Müller; Claus Schnabel (Kiel Institute for the World Economy (IfW), 2014)
This paper is the first to show theoretically and empirically how firms' production technology affects the choice of their preferred wage formation regime. Our theoretical framework predicts, first, that the larger the total factor productivity of a firm, the more likely it is to opt for centralized wage formation where it can hide behind less productive firms. Second, the larger a firm's scale elasticity, the higher its incentive to choose centralized rather than decentralized wage setting due to labor cost and straitjacket effects. As firms in Germany are allowed to choose their wage formation regime, we test these two hypotheses with representative establishment data for West Germany. We find that establishments with centralized bargaining agreements indeed have economically and statistically significantly larger total factor productivities and scale elasticities than comparable establishments outside the centralized bargaining regime.
Keywords: J50; J30; J41; 330; wage formation; bargaining; bargaining coverage; Germany